A "Priest King" at Shahr-i Sokhta?. (September 2018) - Vidale, Massimo
Abstract: The paper discusses the published fragment of a statuette made of a buff-grey limestone, recently found on the surface of Shahr-i Sokhta (Sistan, Iran) and currently on exhibit in a showcase of the archaeological Museum of Zahedan (Sistan-Baluchistan, Iran). Most probably, it belongs to a sculptural type well known in some sites of Middle and South Asia dating to the late 3rd-early 2nd millennium BCE - a male character sitting on the right heel, with the left hand on the raised left knee, and a robe leaving bare the left shoulder. Preliminary comments on the cultural, historical and chronological implications of this important find are included.